Potential transformation of baduy local wisdom values in civics education learning in elementary school - Elan Elan; Elis Solihati (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2022)
Indonesia has diverse values rooted in local wisdom, for instance, the local wisdom of the Baduy ethnic group. Baduy local wisdom has the potential values to be a transformation source in Civics Education learning. This study aimed to describe the potential transformation of Baduy local wisdom in Civics Education learning.  A case study,  a qualitative approach was employed in this study.  This research is located at elementary schools around Citorek district, Lebak, Banten. The data was obtained through interviews, observations, and documentation.  The results showed that Baduy local wisdom taught lessons to be a good citizen because it contains the following values: first, Baduy local wisdom forms the basic human characters of children aged 6 to 12 years. Second: Baduy teachings are universal and religious to shape children's morality,, especially boys. The revitalization of the values of Baduy cultural tradition needs to be transformed by today's young generation in their social life. These values can be transformed in the learning process of Civics education. One of the efforts made is through strengthen the ability of teachers to design the lesson plans, syllabus, and learning methods that were adapted to the context of deep local wisdom values.